Risky Asset Holdings During Covid-19 and their Distributional Impact: Evidence from Germany - Lukas Menkhoff; Carsten Schröder (Review of Income and Wealth, 2021)
We present evidence from a repeated survey on risky asset holdings carried out on a representative sample of the German population six times between April and June 2020. Given the size of the Covid-19 shock, we find little evidence of portfolio rebalancing in April 2020. In May, however, individual investors started buying heavily, parallel to market recovery. The cross-section shows large differences as young, educated, high income, and risk tolerant investors are net buyers throughout and, thus, benefit from the stock market recovery. Older individuals, parents of young children, and individuals affected by adverse liquidity shocks from Covid-19 are net sellers. Given the high risk of illness, older people are hit by dual blows to both health and finances.
Keywords: 330; risky assets; distributional effects; individual investment behavior; health and income shocks; expected adverse shocks